The vitamin B12 processing enzyme, mmachc, is essential for zebrafish survival, growth and retinal morphology. (18th March 2020) - Sloan, Jennifer L; Achilly, Nathan P; Arnold, Madeline L; Catlett, Jerrel L; Blake, Trevor; Bishop, Kevin; Jones, Marypat; Harper, Ursula; English, Milton A; Anderson, Stacie; Trivedi, Niraj S; Elkahloun, Abdel; et al.
Abstract: Cobalamin C ( cblC ) deficiency, the most common inborn error of intracellular cobalamin metabolism, is caused by mutations in MMACHC, a gene responsible for the processing and intracellular trafficking of vitamin B12. This recessive disorder is characterized by a failure to metabolize cobalamin into adenosyl- and methylcobalamin, which results in the biochemical perturbations of methylmalonic acidemia, hyperhomocysteinemia and hypomethioninemia caused by the impaired activity of the downstream enzymes, methylmalonyl-CoA mutase and methionine synthase. Cobalamin C deficiency can be accompanied by a wide spectrum of clinical manifestations, including progressive blindness, and, in mice, manifests with very early embryonic lethality. Because zebrafish harbor a full complement of cobalamin metabolic enzymes, we used genome editing to study the loss of mmachc function and to develop the first viable animal model of cblC deficiency. mmachc mutants survived the embryonic period but perished in early juvenile life. The mutants displayed the metabolic and clinical features of cblC deficiency including methylmalonic acidemia, severe growth retardation and lethality. Morphologic and metabolic parameters improved when the mutants were raised in water supplemented with small molecules used to treat patients, including hydroxocobalamin, methylcobalamin, methionine and betaine. Furthermore, mmachc mutants bred to express rod and/or cone fluorescent reporters, manifested a retinopathy and thin optic nerves (ON). Expression analysis using whole eye mRNA revealed the dysregulation of genes involved in phototransduction and cholesterol metabolism. Zebrafish with mmachc deficiency recapitulate the several of the phenotypic and biochemical features of the human disorder, including ocular pathology, and show a response to established treatments.